Evaluating the Biotic Integrity of Watersheds in the Sierra Nevada, California - Peter B. Moyle; Paul J. Randall (Conservation Biology, 1998)
We developed a watershed index of biotic integrity that used whole watershed variables for metrics rather than site‐specific variables. We used the index to evaluate the biological health of 100 watersheds in the Sierra Nevada of California. The index scores, which were based on various measures of distribution and abundance of native fish and frogs, indicated that 7 of the watersheds were in excellent condition (high biotic health), 36 were in good to very good condition, 48 were in fair condition, and 9 were in poor condition. The biggest factors contributing to low index scores were large dams and introduced fishes, although measures of road density and indicators of intensity of use of terrestrial habitats were also important. Large areas of the Sierra Nevada that were once fishless now contain trout in most waters, anadromous fishes are excluded from many streams from which they were once abundant, assemblages of native fishes have been disrupted, and ranid frogs have been extirpated from many areas. All watersheds in the Sierra Nevada have thus experienced loss of biotic integrity, but some have suffered much less than others. Evaluations of the biotic integrity of watersheds over wide regions can help managers set priorities for watershed‐oriented systems of aquatic conservation and provide starting places for more‐intensive studies. Evaluación de la Integridad Biótica de Cuencas Acuíferas en la Sierra Nevada, California Un indice de cuencas de integridad biótica fue desarrollado, el cual utilizó variables paramétricas en vez de variables de lugar específico. El índice fue utilizado para evaluar la salud biológica de cien cuencas en la Sierra Nevada de California. El muestreo, el cual fue basado en varias medidas de disribución y abundancia de peces nativos y ranas indicaron que siete de las cuencas estaban en excelente condición (salud biótica), treinta y seis estaban de buena a muy buena condición, cuarenta y ocho estaban en favorable condición y nueve estaban en mala condición. Los factores más grandes que contribuyeron al bajo muestreo fueron represas grandes y peces introducidos, aunque medidas de densidad de carreteras, indicadores de intensidad del uso de comunidades terrestres, fueron también importantes. Grandes areas de la Sierra Nevada que no tenían peces ahora contienen trucha en la mayoria de sus aguas, peces anadromos están excluidos de muchos arroyos, en los cuales ellos fueron una vez abundantes; comunidades de peces nativos han sido interrumpidas, y ranas de la familia ranidae han sido exterminadas de muchas areas. Todas las cuencas en la Sierra Nevada, por lo tanto, han experimentado pérdida de integridad biótica, pero algunas han experimentado menos pérdida que otras. Evaluaciones de la integridad biótica de cuencas sobre regiones extensas pueden ayudar a establecer prioridades para un sistema de conservación acuática y proveer información básica para estudios más intensos.